Messages of Religious Moderation Education in Sambas Islamic Manuscripts - Erwin Mahrus; Zaenuddin Hudi Prasojo; B. Busro (Jurnal Madania)
In the beginning of the 20th century, West Kalimantan had a number of social issues, especially in the context of religious moderation. Both individuals and groups claim one another as being the most proper ones. Fom that condition, a negative impact occurred on social order in society. Observing to this situation, Muhammad Basiuni Imran, the Maharaja Imam to the Kingdom of Sambas, initiated a meeting of Islamic religious leaders and priests for the Western part of Borneo. This work is based on research conducted on manuscripts that recorded the speeches of West Kalimantan religious leaders and priests (alim ulama) in the meeting. Considering that this study is aimed at exploring the manuscripts, to approach the issue the authors employ philology that includes the inventory of manuscripts, identification of origins, compiling descriptions, making text summaries, and finally presenting messages of religious moderation education in the related texts. This study successfully concludes that those Islamic manuscripts of Sambas in West Kalimantan, including the manuscript by Maharaja Imam Sambas are on the end of extinction due to ages of century. The text is full of messages of religious moderation education as seen in the principle of flexibility and renewal (tajdîd), the principle of ease (taysîr), and the principle of tolerance (tasâmuh). Finally, the madrasa founded by Maharaja Imam Sambas is as among the oldest Islamic education institution that promotes religious moderation in West Kalimantan.